PENGGUNAAN BAHAN TAMBAHAN PANGAN (BTP) PADA IBU RUMAH TANGGA DI KELURAHAN PEJANGGIK KOTA MATARAM - MUHAMMAD NIZHAR NAUFALI; NI WAYAN PUTU MEIKAPASA; RINA HELDIYANTI (Universitas Mahasaraswati K. Mataram, 2023)
Problems of food additives are one component of various nutritional problems in society. The main cause is a lack of understanding and knowledge from the food industry players, followed by a lack of user or consumer attention to the quality and safety of the food consumed. Housewives play a very important role in the quality and safety of food within the family. This study aims to determine the extent about the housewives knowledge of using food additives. This research was conducted using a survey method with respondents who have children under five in the West Pajang Environment, Pejanggik Subdistrict, Mataram. The data collected from 66 respondents was obtained with Ms. Excel 2010. The results of the study indicated that the knowledge of mothers in the Pajang Barat environment, Pejanggik Subdistrict, Mataram City, regarding the use of BTP was in the very good category, especially in the definition of BTP, the types of preservatives and the effects of using BTP in the long term. Meanwhile, the attitude of the mothers has been good, except for the attitude to pay attention to the packaging labels before buying snacks. From these results we can be seen that there is a tendency between education, level of knowledge and attitudes shown by mothers in West Pajang regarding the use of good food additives